Examining Science Learning Motivation in Elementary School Students: A Cross-Sectional Study with Rasch Analysis - Fathia Azzahra; Rohmani (Universitas Pendidikan Ganesha, 2024)
Learning motivation is a key factor in students' academic success, particularly in science education at the elementary school level. However, variations in students' motivation levels indicate the need for further analysis to understand the factors influencing it. This study aims to investigate the learning motivation of fifth-grade elementary school students in science education using Rasch model-based analysis. This research employs a descriptive study with a cross-sectional design, involving 73 students as research subjects. Data were collected through a questionnaire designed to measure four key indicators of learning motivation: self-efficacy, interest and enjoyment, connection to daily life, and cross-cultural interactions. The analysis results indicate that, overall, students' learning motivation falls within the high category, with the cross-cultural interactions (CCI) indicator recording the highest score at 80%, followed by interest and enjoyment (IE) at 75%. The self-efficacy (SE) and connection to daily life (CDL) indicators scored slightly lower but remained in the high category, at 70% each. Rasch analysis confirmed that the questionnaire demonstrated excellent reliability (0.91 for items and 0.83 for respondents) and validity aligned with the measurement model. These findings suggest that learning approaches that enhance cross-cultural interactions and student interest can serve as effective strategies for improving motivation in science education.